The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1108/eum0000000004544
|View full text |Cite
|
Sign up to set email alerts
|

The usage and portrayal of older models in contemporary consumer advertising

Abstract: IntroductionAs the population of North America, Europe and Australia continues to mature, marketers in these countries have started to recognise that there is a need to move attention towards this potentially lucrative group of consumers. To date, most of the consumer research into the over-50s market has taken place in the USA, with few studies being carried out to investigate the UK mature market. Given the current and potential importance of this affluent and discriminating group of consumers, one would exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
2
7

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 35 publications
5
35
2
7
Order By: Relevance
“…At the same time, and again consistent with the extant research (Carrigan & Szmigin, 1998;Lumme-Sandt, 2011;McConatha et al, 1999;Zhang et al, 2006), we also found that when older men were present, they were depicted almost exclusively in a favorable light and in similar ways across the six magazines irrespective of the target readerships or frequency of the portrayals. Specifically, our visual thematic analysis revealed two primary ways that older men were depicted, namely, as experienced and powerful or as healthy and happy.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…At the same time, and again consistent with the extant research (Carrigan & Szmigin, 1998;Lumme-Sandt, 2011;McConatha et al, 1999;Zhang et al, 2006), we also found that when older men were present, they were depicted almost exclusively in a favorable light and in similar ways across the six magazines irrespective of the target readerships or frequency of the portrayals. Specifically, our visual thematic analysis revealed two primary ways that older men were depicted, namely, as experienced and powerful or as healthy and happy.…”
Section: Discussionsupporting
confidence: 89%
“…In line with previous research (Carrigan & Szmigin, 1998;Gantz et al, 1980;Harwood & Roy, 1999;Kvasnicka et al, 1982;Peterson, 1992;Roberts & Zhou, 1997;Williams et al, 2010;Zhang et al, 2006;Zhou & Chen, 1992), our content analysis revealed that older adults were largely absent from men's magazines, with the exception of Zoomer. Indeed, older individuals comprised the following percentages of the images of people within the six magazines we analyzed: 27% in Esquire, 14% in GQ, 10% in Maxim, 6% in Men's Health, 18% in Men's Journal, and 71% in Zoomer.…”
Section: The Absence Of Older Mensupporting
confidence: 79%
“…Therefore, business marketing teams in China focused their attention on younger consumers and children but ignored older consumers of age 50 and above (Carrigan & Szmigin, 1998;Guo & Yu, 1999;Long, 1998). Chinese researchers also focused their studies on children's consumption patterns (Guan, 2003;Sun, 2003).…”
mentioning
confidence: 98%
“…A wealth of research has examined how various media, including advertising, films, print media, and television portray older adults and reinforce cultural assumptions about later life (see for example, Carrigan & Szmigin, 1998;Lumme-Sandt, 2011;Powell, 2013;Zhang et al, 2006). While older adults continue to be underrepresented in magazine and newspaper advertising and television commercials (Carrigan & Szmigin, 1998;Zhang et al, 2006), collectively the various media entrench youth-based, heteronormative standards of sexuality (de Luce, 2001;Lewis, Medvedev, & Seponski, 2011). Print media, television advertisements, contemporary romance novels, and films primarily feature thin, physically attractive, able-bodied, young women who are held up as the epitome of feminine beauty and sexual desirability (de Luce, 2001;Lewis et al, 2011;Ménard & Cabrera, 2011).…”
Section: Media Portrayals Of Later Life Sexualitymentioning
confidence: 99%